In vitro cytotoxicity evaluation of cadmium by label‐free holographic microscopy. Issue 12 (25th September 2018) - Mugnano, Martina; Memmolo, Pasquale; Miccio, Lisa; Grilli, Simonetta; Merola, Francesco; Calabuig, Alejandro; Bramanti, Alessia; Mazzon, Emanuela; Ferraro, Pietro
Abstract : Among all environmental pollutants, the toxic heavy metal cadmium is considered as a human carcinogen. Cadmium may induce cell death by apoptosis in various cell types, although the underlying mechanisms are still unclear. In this paper we show how a label‐free digital holography (DH)‐based technique is able to quantify the evolution of key biophysical parameters of cells during the exposure to cadmium for the first time. Murine embryonic fibroblasts NIH 3T3 are chosen here as cellular model for studying the cadmium effects. The results demonstrate that DH is able to retrieve the temporal evolution of different key parameters such as cell volume, projected area, cell thickness and dry mass, thus providing a full quantitative characterization of the cell physical behaviour during cadmium exposure. Our results show that the label‐free character of the technique would allow biologists to perform systematic and reliable studies on cell death process induced by cadmium and we believe that more in general this can be easily extended to others heavy metals, thus avoiding the time‐consuming, expensive and invasive label‐based procedures used nowadays in the field. In fact, pollution by heavy metals is severe issue that needs rapid and reliable methods to be settled. Abstract : According to the International agency for Research on Cancer, cadmium (Cd) is considered as a human carcinogen. Cadmium may induce cell death by apoptosis in various cell types, although the underlying mechanisms are still unclear. In this work, we present a label‐free digital holography (DH)‐based technique as an in vitro cytotoxicity assay, which overcomes the limitations of conventional in vitro test based on colour or fluorescence read outs.